Information Research at 30: its role as a diamond open access journal supporting scholarly communication in library and information science - Yoon, JungWon; Andrews, James E.; Chung, EunKyung (Information Research an international electronic journal, 2025)
Introduction. This paper examines the contributions of Information Research as a diamond open access (OA) journal within the library and information science field. Method. The dataset was extracted from the Web of Science Core Collection. Results. The journal’s commitment to geographical diversity, its sustained journal impact and its role as a scholar-led publisher were revealed. Conclusion(s). The journal demonstrates the potential of diamond open access publishing while maintaining high impact and visibility.